2022
DOI: 10.4103/jos.jos_94_21
|View full text |Cite
|
Sign up to set email alerts
|

Ingestion of orthodontic appliances

Abstract: Ingestion is the entry of a substance into the human organism, which occurs by taking it through the mouth into the gastrointestinal tract. One of the adverse events that may happen during the course of an orthodontic treatment is the ingestion of orthodontic appliances. The present review aims to investigate the literature regarding the ingestion of orthodontic appliances. An electronic search was carried out in order to identify case reports of ingestion of foreign objects related to orthodontic treatment in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Karmani et al reported that patients who are more prone to the ingestion of orthodontic appliances are those suffering from intellectual disability, epileptic seizures, hyperkinetic disorder, an intense vomit reflex, and panic attacks. 9 Furthermore, a patient lying in the supine position increases the risk of aspiration during dental treatment. 13 In a 10-year institutional review study, Tiwana et al observed that among all dental specialties, fixed prosthodontic treatment had the highest frequency of negative outcomes, followed by orthodontic treatment.…”
Section: Accidental Aspiration Of Foreign Bodies In Orthodontic Denti...mentioning
confidence: 99%
See 2 more Smart Citations
“…Karmani et al reported that patients who are more prone to the ingestion of orthodontic appliances are those suffering from intellectual disability, epileptic seizures, hyperkinetic disorder, an intense vomit reflex, and panic attacks. 9 Furthermore, a patient lying in the supine position increases the risk of aspiration during dental treatment. 13 In a 10-year institutional review study, Tiwana et al observed that among all dental specialties, fixed prosthodontic treatment had the highest frequency of negative outcomes, followed by orthodontic treatment.…”
Section: Accidental Aspiration Of Foreign Bodies In Orthodontic Denti...mentioning
confidence: 99%
“…1 The reported aspirated orthodontic appliances are the expansion key, archwire and archwire segments, fixed orthodontic brackets, removable appliances, retainer, twin block, orthodontic band material and molar bands and mini screws. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Some accidents happen in the dental clinic due to the operator's carelessness, while others happen outside the clinic. In a systematic review, 617 cases reported by 45 articles showed that aspirated and ingested dental material cases were more common in older patients.…”
Section: Accidental Aspiration Of Foreign Bodies In Orthodontic Denti...mentioning
confidence: 99%
See 1 more Smart Citation
“…Dental‐related objects rank second in the list of frequently ingested or aspirated foreign bodies in adults 1 such as endodontic instruments, prosthesis, extracted teeth, and orthodontic components 2 like bands, brackets, buccal tubes, removable appliances, appliance fragments, archwire fragments, transpalatal arches, sectional archwires, expansion appliance keys, coil springs, retainers, and quadhelices 3 . Patient position on the dental chair during treatment such as the supine or semirecumbent position is an important risk factor for these incidents 4 .…”
Section: Introductionmentioning
confidence: 99%
“…The patient should also be informed of the possible need for extraction of teeth, surgical procedures, and the possibility of relapse [25][26][27][28]. Other risks during orthodontic treatment include appliance breakage; detached brackets; broken or protruding wires as well as the possibility of swallowing detached brackets or other orthodontic appliances [29,30]. Lately, the possibility of transmission of infectious diseases within the dental office like Covid -19 has also been given particular attention [31].…”
Section: Introductionmentioning
confidence: 99%